2021
DOI: 10.1002/ehf2.13161
|View full text |Cite
|
Sign up to set email alerts
|

Modification of ventriculo–arterial coupling by spironolactone in nonischemic dilated cardiomyopathy

Abstract: Aims We sought to clarify the role of ventriculo-arterial (V-A) coupling in the treatment of nonischemic dilated cardiomyopathy (NIDCM) by adding a mineralocorticoid receptor antagonist (MRA) to conventional anti-failure therapy. Methods and results We employed cardiac magnetic resonance imaging to quantify left ventricular (LV) contractility and V-A coupling in normal subjects at rest (n = 11) and in patients with NIDCM (n = 12) before and after long term anti-failure therapy, in which MRA was added to conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…[20] This outcome can indicate and emphasize the conclusion that HA is a reversible factor of heart remodeling and must be cured. MRA also turned out to improve LVEF [21] and reduce peripheral vascular disease due to arterial elastance improvement and inhibition of myocardial collagen synthesis. [22] The significance of the presence of HA stands in contrast to the results from the other research, which was mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…[20] This outcome can indicate and emphasize the conclusion that HA is a reversible factor of heart remodeling and must be cured. MRA also turned out to improve LVEF [21] and reduce peripheral vascular disease due to arterial elastance improvement and inhibition of myocardial collagen synthesis. [22] The significance of the presence of HA stands in contrast to the results from the other research, which was mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that the administration of certain drugs (e.g., Sacubitril-Valsartan, Carvedilol, or Spironolactone) improves the E a /E es ratio, and thus, VAC in addition to their known clinical benefits [46][47][48][49].…”
Section: Chronic Heart Failure With Reduced Ejection Fractionmentioning
confidence: 99%
“…98,99 This is through the amelioration of the adverse effects of aldosterone that promotes LV hypertrophy and fibrosis. Spironolactone has demonstrated volumetric reverse remodelling in HFrEF when assessed by TTE [100][101][102] and CMRI. 103 In non-ischaemic cardiomyopathy, the mineralocorticoid receptor antagonist (MRA) dose may influence remodelling, with a high dose spironolactone therapy resulting in a greater improvement in LVEDV, LVEDD, and LVEF than low dose.…”
Section: Mineralocorticoid Receptor Antagonistmentioning
confidence: 99%